Velvet Bean (Mucuna pruriens var. utilis) a Cover Crop as Bioherbicide to Preserve the Environmental Services of Soil - Ceballos, Angel Isauro Ortiz; Rivera, Juan Rogelio Aguirre; Arce, Mario Manuel Osorio; Valdivia, Cecilia Peña (IntechOpen, 2012)
None